The historical novel as a specific fictional world - some methodological remarks - Stanovsky, Jaroslav (Romanica Olomucensia, 2020)
The historical novel, in vogue from the beginning of the 19th century, represents a specific literary genre, situated between fiction and (historical) reality. This paper examines the possibilities of this genre through the theory of fictional worlds. The fictional narrative, including the historical novel, already differs from the factual narrative in that it is the fruit of the invention of the writer and its relation to reality is thus specific. Fiction, obviously, is not just an imitation of reality and mimetic theories cannot sufficiently explain the nature of the fictional referent. The theory of fictional worlds, which supposes the existence of a specific universe generated by the text of the novel, offers a more appropriate concept for analysing and explaining fictional narratives. However, the conception of this theory based on a strict separation of fictional worlds and reality is not applicable to historical novels, for at least two reasons. First, historical novels are read as representations of history by their readers. Second, historical novels refer constantly to an extratextual reality, as demonstrated by the differences between the historical characters and the purely invented characters. It is therefore possible to consider historical novels as a special type of fictional world. They refer to, but do not depend on, historical reality and can thus contribute to the creation of ``historical myths''.
Keywords: theory of fiction; fictional worlds; historical novel; 19th century; myths